Bumiputera investment a critical appraisal in the context of achieving the objectives of new economic policy by 1990 - Ismail, Zainuddin (1990)
I would like to express my sincere gratitude to those who have given their full co-operation and valuable iraforraation and advice to my research project. Firstly, I would like to convey my greatest appreciation to my advisor, Puan Zawiah Laidin, to my lecturer. Dr. Abdul Razak Abdul and to my tutor En. Mohd. Tahir Abdul Hamid, for their invaluable guidance and advice. Thanks are due to those whom I have interviewed especially Encik Zulkifly Zabidin, Manager of Permodalan Nasional Berhad, Encik Rahim Aziz, Research Manager Komplek Kewangan Malaysia Berhad, Encik Ahmad Sarkam, the Secretary of Coordinating Council for Small Industries, and also those wïiose names are not mention here together to the various agencies and companies for their assistance in the process of my research. Lastly my acknowledgement goes to those who have in a way, either directly or indirectly constributed and assisted me in my research.